Zero-ending prices, cognitive convenience, and price rigidity - Avichai Snir; Haipeng Chen; Daniel C. Levy (Bar-Ilan University, Department of Economics, 2022)
We assess the role of cognitive convenience in the popularity and rigidity of 0-ending prices in convenience settings. Studies show that 0-ending prices are common at convenience stores because of the transaction convenience that 0-ending prices offer. Using a large store-level retail CPI data, we find that 0-ending prices are popular and rigid at convenience stores even when they offer little transaction convenience. We corroborate these findings with two large retail scanner price datasets from Dominick's and Nielsen. In the Dominick's data, we find that there are more 0-endings in the prices of the items in the front-end candies category than in any other category, even though these prices have no effect on the convenience of the consumers' check-out transaction. In addition, in both Dominick's and Nielsen's datasets, we find that 0-ending prices have a positive effect on demand. Ruling out consumer antagonism and retailers' use of heuristics in pricing, we conclude that 0-ending prices are popular and rigid, and that they increase demand at convenience settings, not only for their transaction convenience, but also for the cognitive convenience they offer.
Keywords: E31; L16; D90; E70; M30; 330; Cognitive Convenience; Transaction Convenience; Price Rigidity; Price Stickiness; Sticky Prices; Rigid Prices; 0-Ending Prices; Round Prices; Convenient Prices; 9-Ending Prices; Just Below Prices; Psychological Prices; Price Points